Improving students’ metacognitive and self-efficacy in learning Biology through reducing academic stress and cognitive anxiety using IBSR technique - Azura Salsabila; Adi Rahmat; Yanti Hamdiyati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Student academic stress can impact class participation. Integrating psychological treatment into learning strategies can help manage academic stress. The objective of this research is to enhance students' metacognitive and self-efficacy by reducing their learning difficulties and cognitive anxiety. This will be achieved by integrating Inquiry-Based Stress Reduction (IBSR) into learning strategies, which will help to alleviate academic stress during the learning process. The study is designed as a quasi-experimental study using a pretest-posttest nonequivalent control group design. The study was conducted at Bandung City State High School with the participation of 70 class XI MIPA students from two different classes, 35 in the experimental class and 35 in the control class.  Both classes utilized problem-based learning (PBL), with the experimental class receiving the IBSR technique at the beginning of learning and various stages of core PBL activities. A questionnaire rating scale with 8 scales was used to collect data on academic stress, learning difficulties, cognitive anxiety, and student self-efficacy. Additionally, students' metacognitive abilities were measured using an open-ended essay. After two weeks of learning, the IBSR psychological intervention in the experimental class had lower student learning difficulties and cognitive anxiety than the control class. The IBSR psychological intervention in the experimental class on students' self-ability and metacognitive abilities also had higher results than the control class.  The research suggests that teachers should consider psychological interventions when implementing learning innovations that improve student learning performance.